2019
DOI: 10.1097/pts.0000000000000567
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Safety Scale Perceived by the Witness of Prehospital Emergency Care

Abstract: Objective The aim of the study was to design and validate a new tool to measure the security perceived by witnesses of patient care and hospital transfers, after requesting urgent assistance via the “061” phone number. Methods This is a descriptive observational, cross-sectional, design, and validation study of a scale conducted by telephone interview. Witnesses of urgent assistance and transfers by prehospital emergency medical services in the province… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 10 publications
1
12
0
2
Order By: Relevance
“…The results suggest that most of the patients in this study taken to hospital after requesting urgent prehospital care felt safe or very safe, which is consistent with the results of previous studies (Péculo‐Carrasco et al, 2013, 2019), as well as with the biannual satisfaction survey conducted by the prehospital emergencies service in Andalusia among assisted patients (Public Company for Health Emergencies, 2018). Defining the perception of safety was not easy for either patients or professionals.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results suggest that most of the patients in this study taken to hospital after requesting urgent prehospital care felt safe or very safe, which is consistent with the results of previous studies (Péculo‐Carrasco et al, 2013, 2019), as well as with the biannual satisfaction survey conducted by the prehospital emergencies service in Andalusia among assisted patients (Public Company for Health Emergencies, 2018). Defining the perception of safety was not easy for either patients or professionals.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies following a quantitative methodology with questionnaires and scales (González‐Cabrera et al, 2014; Mira et al, 2009; Péculo‐Carrasco et al, 2013, 2019), and a qualitative methodology with focus group techniques and semi‐structured interviews (Granström et al, 2019; Lovink et al, 2015; Mollon, 2014; Oliveira Arruda et al, 2017; Prieto Rodríguez et al, 2008) have been published in recent years that aim to discover the opinions, perceptions and experiences of patients regarding clinical safety in different healthcare settings. Comparing the results of these studies with research in which healthcare professionals themselves revealed their perceptions of safety, the responses were seen to differ.…”
Section: Introductionmentioning
confidence: 99%
“…Data were collected by means of interviews (Ahl & Nyström, 2012; Jepsen et al, 2019; Lundqvist et al, 2021; Venesoja et al, 2020), semi‐structured interviews (Kingswell et al, 2015; Magnusson & Granskar, 2005) and focus groups (Péculo‐Carrasco et al, 2020). The three articles with a quantitative methodology followed a cross‐sectional descriptive observational design (Péculo‐Carrasco et al, 2013, 2021; Salminen‐Tuomaala et al, 2018), with sample sizes between 169 and 1011 subjects. In two of these, scales were validated that measure perceived safety in pre‐hospital emergencies (Péculo‐Carrasco et al, 2013, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Pre‐hospital emergencies were the most frequent context, either with a hospital transfer (Ahl & Nyström, 2012; Jepsen et al, 2019; Péculo‐Carrasco et al, 2013, 2021; Péculo‐Carrasco et al, 2020; Venesoja et al, 2020) or without (Salminen‐Tuomaala et al, 2018). The setting for the three remaining articles was the transfer of patients between hospitals (Kingswell et al, 2015; Lundqvist et al, 2021; Magnusson & Granskar, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The sample of 55 women on whom we validated the scale was considered sufficient given the number of births at the hospital where the study was conducted. Other studies have validated scales with a similar or even smaller numbers of participants [1,50,51].…”
Section: Discussionmentioning
confidence: 99%